Implementation of Excellent Service for Bumd Employees in Increasing Customer Trust in Tapin Bank in Tapin City, South Kalimantan - Shelda Arianti (International Journal of Economics Business and Social Sciences, 2026)
This study aims to analyze the excellent service practices applied by Bank Tapin employees and their influence on customer experience, perception, and trust. The method used is a qualitative approach with a type of case study through observation techniques, in-depth interviews, and documentation. The results of the study show that excellent service at Bank Tapin in general has been running well, characterized by a friendly attitude, effective communication, empathy, and the ability to build positive interpersonal relationships with customers. Customer experiences and perceptions of service quality also tend to be positive, especially in the initial impression of service, information transparency, and transaction security guarantees. However, there are still several obstacles, such as long queue times, limited facilities, less than optimal digital services, and uneven employee competence in understanding complex banking products. The implementation of excellent service has proven to have a significant effect on building and maintaining customer trust, where professional attitude, service reliability, and transparency are the main factors. Despite some shortcomings, the quality of humanistic interaction is able to maintain the level of customer trust. Therefore, improvements are needed in the operational, technological, and human resource competencies to optimize service quality and strengthen customer loyalty in a sustainable manner.